Association between electrocardiographic features and mortality in COVID‐19 patients. Issue 4 (19th March 2021) - Antwi‐Amoabeng, Daniel; Beutler, Bryce D.; Singh, Sahajpreet; Taha, Moutaz; Ghuman, Jasmine; Hanfy, Ahmed; Manasewitsch, Nicholas T.; Ulanja, Mark B.; Ghuman, Joban; Awad, Munadel; Gullapalli, Nageshwara; Gbadebo, T. David
Abstract: Background: Cardiovascular events have been reported in the setting of coronavirus disease‐19 (COVID‐19). It has been hypothesized that systemic inflammation may aggravate arrhythmias or trigger new‐onset conduction abnormalities. However, the specific type and distribution of electrocardiographic disturbances in COVID‐19 as well as their influence on mortality remain to be fully characterized. Methods: Electrocardiograms (ECGs) were obtained from 186 COVID‐19‐positive patients at a large tertiary care hospital in Northern Nevada. The following arrhythmias were identified by cardiologists: sinus bradycardia, sinus tachycardia, atrial fibrillation (A‐Fib), atrial flutter, multifocal atrial tachycardia (MAT), premature atrial contraction (PAC), premature ventricular contraction (PVC), atrioventricular block (AVB), and right bundle branch block (RBBB). The mean PR interval, QRS duration, and corrected QT interval were documented. Fisher's exact test was used to compare the ECG features of patients who died during the hospitalization with those who survived. The influence of ECG features on mortality was assessed with multivariable logistic regression analysis. Results: A‐Fib, atrial flutter, and ST‐segment depression were predictive of mortality. In addition, the mean ventricular rate was higher among patients who died as compared to those who survived. The use of therapeutic anticoagulation was associated with reduced odds of death; however, this association did not reach statistical significance. Conclusion: The underlying pathogenesis of COVID‐19‐associated arrhythmias remains to be established, but we postulate that systemic inflammation and/or hypoxia may induce potentially lethal conduction abnormalities in affected individuals. Longitudinal studies are warranted to evaluate the risk factors, pathogenesis, and management of COVID‐19‐associated cardiac arrhythmias.